Pengaruh Transparansi Laporan Keuangan, Akuntabilitas Pengelolaan Dana Terhadap Tingkat Kepercayaan Muzakki untuk Membayar Zakat Pada LAZ Inisiatif Zakat Sumut - Cahyani, Nur (Jurnal Manajemen Akuntansi (JUMSI), 2024)
This study aims to empirically examine the effect of accountability, transparency and zakat management on muzakki's interest in LAZ North Sumatra Zakat Initiative. The variables used in this study are the independent variables (accountability, transparency and fund management) while the dependent variable (Muzakki's Trust). The data source in this study is primary data where the data collection method uses a questionnaire that is distributed online via Googleform. The number of samples whose data was successfully processed was 89 people. The sample selection method used is the non-probability method, namely convenience sampling, which is a sampling technique based on the ease of accessing members of the population. The results of this study indicate that the T-test of two variables, namely transparency and fund management, has a positive effect, while accountability has no effect on the level of muzakki's trust. And the results of the F test simultaneously have a significant effect on muzakki's interest in North Sumatra's Zakat Initiative LAZ.